6m + 7m = 8 - m - 8
13m = 8 - m - 8
14m = 8 - 8
14m = 0
m = 0 / 14
m = 0
2006-11-24 06:47:33
·
answer #1
·
answered by Jen 2
·
0⤊
0⤋
6m+7m+m = 8-8
14m = 0
m =0
2006-11-24 13:37:45
·
answer #2
·
answered by azka a 2
·
0⤊
0⤋
It can be true or false. True if m=0; false otherwise.
The question does not ask what m is; it asks what would the statement "6m+7m=8-m-8" be; in other words, the truth value of the statement. Zero does not answer the question.
2006-11-24 14:26:00
·
answer #3
·
answered by Jack 2
·
0⤊
0⤋
6m + 7m = 8 - m - 8 combine like terms
13m=-m add m
14m=0 divide by 14
m=0
2006-11-24 14:30:07
·
answer #4
·
answered by yupchagee 7
·
0⤊
0⤋
m = 0
2006-11-24 13:49:51
·
answer #5
·
answered by ag_iitkgp 7
·
0⤊
0⤋
6m + 7m = 8 - m - 8
13m = -m
14m = 0
m = 0
2006-11-24 13:36:58
·
answer #6
·
answered by blapath 6
·
0⤊
0⤋
6m + 7m = 8 - m - 8
13m = 8 - m - 8
13m + m = 8 - m - 8
14m = 8 - 8
14m = 0
14m/14 = 0/14
m = 0/14
m = 0
The answer is m = 0
- - - - - -s-
2006-11-24 14:53:02
·
answer #7
·
answered by SAMUEL D 7
·
0⤊
0⤋
14 m = 0 ?
steps_
13 m =- m+ 0 (the two 8s cancel each other)
14 m = 0
2006-11-24 13:37:26
·
answer #8
·
answered by asds 3
·
0⤊
0⤋
im guessing 0
2006-11-24 13:37:11
·
answer #9
·
answered by Mad Jack Wants To Help. 2
·
0⤊
0⤋
when you add up left side you have 13m, when you add up right side you have left - m
13m equals -m only when m = 0
because 13 zeros equal zero and - zero equals zero too.
2006-11-24 13:42:27
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋